Herramientas tecnológicas y su influencia en el proceso de enseñanza aprendizaje en los estudiantes de la Escuela Teresa Ala Vedra Itama - Torres Pineda, Roxana Anabel (2022)
The main objective of this research work is to determine the way in which the free educational technological tools Emaze, GoConqr and Educaplay influence the teaching-learning process in the students of the Teresa Alavedra Itama School in such a way that teachers have options to support its contents through the use of these tools in order to achieve the expected academic performance. The type of research that was applied according to its design is non-experimental because the study variables were not manipulated but rather the result of the relationship of the two variables was observed. According to its scope, this research is descriptive because it allowed me to collect the necessary information to analyze it and interpret the results to make decisions, in the same way the correlational research was applied that allowed me to measure the relationship of these variables. The sample consisted of 70 students and 4 teachers, the data collection technique was the survey as an instrument was a previously analyzed questionnaire, when validating the results they projected that technological tools and teaching-learning have a significant relationship.